Fuscoporia valenzuelae (Hymenochaetaceae, Basidiomycota), a new species from the tropical dry forest in Mexico - Raymundo, Tania (Instituto de Ecología, A.C., 2021)
Background and Aims: The genus Fuscoporia is characterized by resupinate or pileate basidiomata, dimitic hyphal system, generative hyaline hyphae with encrusted crystals, setal hyphae, hymenial setae and subglobose, ellipsoid or (sub)cylindrical basidiospores. It has a cosmopolitan distribution and sixteen species have been registered from Mexico. The objective of this work was to describe and illustrate Fuscoporia valenzuelae, a new species from the tropical dry forest in Mexico. Methods: The specimens were collected in tropical dry forest in the Chamela-Cuixmala and Sierra Álamos-Río Cuchujaqui Biosphere Reserves. Field data and morphological characteristics were recorded according to traditional techniques in mycology. The material was deposited in the herbarium ENCB of the Escuela Nacional de Ciencias Biológicas of the Instituto Politécnico Nacional. Key results: The new species Fuscoporia valenzuelae was described. It is characterized by resupinate basidiomata of 1.5 m long, a hymenophore with angular to irregular pores (1-2 per mm), presence of hyphal and hymenial setae, and ellipsoid basidiospores. It grows on Astronium graveolens, causing white rot. Conclusions: Fuscoporia with 17 species is the taxon best representing Hymenochaetaceae in Mexico. Fuscoporia valenzuelae is distributed in tropical dry forests of the Pacific Coast.